Meta-Analysis of the Association Between Phosphodiesterase Inhibitors (PDE5Is) and Risk of Melanoma. (19th May 2017) - Loeb, Stacy; Ventimiglia, Eugenio; Salonia, Andrea; Folkvaljon, Yasin; Stattin, Pär
Abstract: The US Food and Drug Administration recently announced the need to evaluate the association between PDE5is and melanoma. We performed a meta-analysis on the association between PDE5i and melanoma using random effects models and examined whether it met Hill's criteria for causality. A systematic search of Medline, EMBASE, and the Cochrane Library from 1998 to 2016 identified three case-control studies and two cohort studies, including a total of 866 049 men, of whom 41 874 were diagnosed with melanoma. We found a summary estimate indicating an increased risk of melanoma in PDE5i users (relative risk = 1.12, 95% confidence interval = 1.02 to 1.23). However, there was no difference in risk between men with low and high exposure to PDE5i, and risk was higher for in situ melanoma than localized and high-risk melanoma, suggesting a lack of dose response and biological gradient. PDE5i use was also associated with basal cell cancer, suggesting a lack of specificity and likely confounding by ultraviolet exposure. Thus, although this meta-analysis found a statistically significant association between PDE5i and melanoma, it did not satisfy Hill's criteria for causality.